Barriers to ESG Standards Implementation in Kazakhstan - Jumasseitova, Assel K.; Alybayeva, Dana (Archives of Business Research, 2025)
This research examines the barriers impeding ESG reporting standards implementation in Kazakhstan through expert analysis (n=10). Utilizing a two-phase evaluation methodology, experts assigned weights (1-5) to factors based on general importance and rated their manifestation (1-10) in Kazakhstan specifically. The study identifies financial limitations (score: 40) as the most significant obstacle, followed by regulatory deficiencies (32), human resource constraints and knowledge gaps (28), information asymmetry (24), methodological limitations (20), organizational resistance (15), and greenwashing (6). The findings reveal a multidimensional challenge landscape where economic constraints and institutional deficits predominate. Based on these results, the research proposes a comprehensive strategy for Kazakhstani companies, including phased implementation with distributed financial burden, proactive regulatory positioning, personnel development, enhanced information transparency, methodological adaptation, and corporate culture transformation. This approach would potentially transform ESG compliance from a regulatory burden into a strategic competitive advantage, enhancing business sustainability and stakeholder appeal in Kazakhstan’s evolving economic landscape.